COMBINATION OF ACUPUNCTURE THERAPY AND TURMERICLIQUORICE HERBS FOR CHRONIC COUGHING CASE - Purwanto, Intan Fahdelasari; Imandiri, Ario; Arifanti, Lusiana (Journal of Vocational Health Studies, 2018)
Background: Coughing is a defense mechanism of the lung against several stimulants as well as to protecting the lung from any trauma. A long period of coughing about more than 8 weeks considered as Chronic coughing. Based on TCM, coughing is a manifestation of the lung which caused by an exogenous factor (such as cold wind and warm wind); and endogenous factor. It is classified as "ke” (coughing with loud sound without producing sputum) and "sou” (coughing with weak sound, however, producing sputum). Purpose:  To know the effect of acupuncture therapy (Hegu LI4, Lieque LU7, Chize LU5) combined with herbs therapy (Curcuma domestica Val. and Glycyrrhiza Glabra L.) to reduce the Chronic coughing period. Method: Acupuncture points were given 12 times within once per 2 days. The herbal therapy was given for 30 days in the form of tea drink twice per day, with a dose of each containing 4gr (1 tea bag). Result: The period of coughing were deteriorating, as well as improving the immune condition which was shown in hematological data of white blood cells. Conclusion: The combined therapy showed to diminish the chronic coughing within 30 days